Anabolic-Androgenic Steroid use in the Nordic Countries: A Meta-Analysis and Meta-Regression Analysis. Issue 1 (February 2015) - Sagoe, Dominic; Torsheim, Torbj⊘rn; Molde, Helge; Andreassen, Cecilie Schou; Pallesen, Ståle
Aims: To investigate the lifetime prevalence and moderators of non-medical AAS use in the five Nordic countries. Methods: We conducted a meta-analysis and meta-regression using studies gathered from searches in PsycINFO, PubMed, ISI Web of Science, Google Scholar, and reference checks. Included were 32 studies that provided original data on 48 lifetime prevalence rates based on a total of 233, 475 inhabitants of the Nordic countries. Results: – The overall lifetime prevalence obtained was 2.1% [95% confidence interval (CI): 1.3-3.4, I 2 = 99.5, P < 0.001]. The prevalence for males, 2.9% (95% CI: 1.7-4.8, I 2 = 99.2, P < 0.001), was significantly higher (Qbet = 40.5, P < 0.001) than the rate for females, 0.2% (95% CI: 0.1-0.4, I 2 = 90.5, P < 0.001). Sweden has the highest prevalence of AAS use: 4.4%, followed by Norway: 2.4%, Finland: 0.8%, Iceland: 0.7%, and Denmark: 0.5%. Country, sample type, and male sample percentage significantly predicted AAS use prevalence in a meta-regression analysis. No indication of publication bias was found. Conclusion: – Though subject to some limitations, our findings suggest that non-medical AAS use should be regarded as a serious public health problem in the Nordic countries.